2017
DOI: 10.14710/reaktor.11.1.45-49
|View full text |Cite
|
Sign up to set email alerts
|

Optimasi Pembuatan Kitosan Dari Kitin Limbah Cangkang Rajungan (Portunus pelagicus) Untuk Adsorben Ion Logam Merkuri

Abstract: Penelitian ini bertujuan untukmenentukan kondisi optimum  factor suhu dan waktu proses deatilasi dari khitin cangkang rajungan (Portunus pelagicus) menjadi khitosan dan mengetahui pengaruh pH adsorpsi dari kitosan terhadap penurunan jumlah ion merkuri (%). Proses deasetilasi dilakukan dengan memanaskan campuran khitin dengan larutan NaOH 50% (rasio 1:20 b/v) pada suhu 70 0C, 80 0C, 90 0C dan 100 0C dengan waktu proses masing-masing 30, 60, 90 dan 120 menit. Parameter respon adalah derajad deasetilasi khitosan.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 2 publications
1
14
0
9
Order By: Relevance
“…The obtained value of deacetylation degree of chitosan in this study was 70.96%. It corresponds well with the degree of deacetylation in Rahayu (2007) for chitosan made from crab shells of 79.65% at 90˚C and a processing time of 120 minutes.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…The obtained value of deacetylation degree of chitosan in this study was 70.96%. It corresponds well with the degree of deacetylation in Rahayu (2007) for chitosan made from crab shells of 79.65% at 90˚C and a processing time of 120 minutes.…”
Section: Resultssupporting
confidence: 65%
“…As an adsorbent, chitosan is able to absorb metal ions such as cadmium, mercury, copper chrome, and nickel. In the experiments conducted by Rahayu (2007), the adsorption using chitosan waste crab shells at pH 2, 3, 4, 5, 6 showed that the higher is pH, the higher the absorbed Mercury concentration. Another research conducted by Tiara (2014) using chitosan for metal adsorption of Pb from mining wastewater in Bangka Belitung stated that the optimum adsorption process was conducted at pH 3 with an adsorption percentage of 80.22%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selain memiliki kelebihan, limbah udang juga memiliki kelemahan sebagai pakan karena mengandung kitin yang cukup tinggi yang bersifat sulit dicerna. Kitin adalah biopolimer dari unit N-asetil-Dglukosamin bewarna putih, tidak berasa, tidak berbau dan tidak larut air, pelarut organik umumnya, asam-asam anorganik dan basa encer (Rahayu dan Purnavita, 2007). Kitin mengikat N dari asam amino penyusun protein sehingga protein menjadi sulit dicerna.…”
Section: Pendahuluanunclassified
“…berhasil mengaplikasikan kitosan untuk menyerap Ni2+,Rahayu (2007) berhasil mengabsorbsi Hg2+,Sanjaya (2007) berhasil mengabsorbsi Pb2+. Nasir dkk.…”
unclassified